2020
DOI: 10.3390/genes11111327
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Potential miRNAs, as Biomarkers for Sepsis and Associated Lung Injury: A Network-Based Approach

Abstract: Sepsis is a dysregulated immune response disease affecting millions worldwide. Delayed diagnosis, poor prognosis, and disease heterogeneity make its treatment ineffective. miRNAs are imposingly involved in personalized medicine such as therapeutics, due to their high sensitivity and accuracy. Our study aimed to reveal the biomarkers that may be involved in the dysregulated immune response in sepsis and lung injury using a computational approach and in vivo validation studies. A sepsis miRNA Gene Expression Omn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…Significantly enriched levels of miR-181a, miR-92a , and miR-424 in the blood of ARDS patients may serve as diagnostic markers, and were found to be closely associated with inflammation and epithelial cell injury [ 58 ]. In numerous sepsis-associated organ injuries, such as those to the lungs, kidneys, and other organs, miRNAs play an important role in cellular signaling, which then regulates the immune response and molecular pathological outcomes [ 59 , 60 ]. Additional studies revealed a significant decrease in the levels of miR-124 in the serum of SLE patients [ 61 ] and an upregulation of miRNA-21 and miR-214 in CRS and CKD patients, respectively [ 26 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly enriched levels of miR-181a, miR-92a , and miR-424 in the blood of ARDS patients may serve as diagnostic markers, and were found to be closely associated with inflammation and epithelial cell injury [ 58 ]. In numerous sepsis-associated organ injuries, such as those to the lungs, kidneys, and other organs, miRNAs play an important role in cellular signaling, which then regulates the immune response and molecular pathological outcomes [ 59 , 60 ]. Additional studies revealed a significant decrease in the levels of miR-124 in the serum of SLE patients [ 61 ] and an upregulation of miRNA-21 and miR-214 in CRS and CKD patients, respectively [ 26 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Much progress has been made in identifying components of the regulatory networks that control lung morphogenesis, including transcription factors, receptors, and miRNAs. miRNAs are endogenous noncoding RNAs with regulatory functions that have shown effects in various lung diseases, such as lung cancer and COPD ( 25 , 26 ). An increasing number of miRNAs are emerging as potential biomarkers for the diagnosis and treatment of lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Adyshev et al suggested that miR-1290 may reduce lung inflammation through targeting nonmuscle myosin light-chain kinase that decreases lung endothelium permeability [116]. Additionally, bioinformatics analysis identified miR-1290 in the set of miRNAs downregulated in serum from sepsis patients [117]. Moreover, it was revealed that the sponging of miR-1290 by hsa_circ_0056558 is involved in the regulation of CDK6 to suppress cell proliferation and differentiation while enhancing apoptosis in ankylosing spondylitis [118].…”
Section: The Role Of Mir-1290 In Non-neoplastic Diseasesmentioning
confidence: 99%